Improving Glucose Tolerance by Reducing Weight Gain in a Polygenic Obese Mouse Model: Use of a High Protein Diet - Blair, A. R.; Strube, M. L.; Proietto, J.; Andrikopoulos, S. (Hormone and Metabolic Research, 2015)
Diets to decrease body weight have limited success in achieving and importantly maintaining this weight loss long-term. It has recently been suggested that energy intake can be regulated by the amount of protein ingested, termed the protein leverage hypothesis. In this study, we determined whether a high protein diet would be effective in achieving and maintaining weight loss in a genetically obese model, the New Zealand Obese (NZO) mouse. NZO and C57BL/6J (C57) control mice were fed a high protein or chow diet for 5 weeks from weaning (3 weeks of age). Body weight and food intake were determined. Mice on the same diet were bred to produce offspring that were fed either a chow or high protein diet. Body weight, food intake, and glucose tolerance were determined. Feeding NZO and C57 mice a high protein diet for 5 weeks resulted in reduced food intake and consequently energy intake and body weight gain compared with mice on a chow diet. NZO mice fed a high protein diet showed a significant improvement in glucose tolerance compared with their chow-fed counterparts, while no difference was seen in C57 mice fed chow or protein diet. The offspring of NZO mice that were fed a high protein diet during gestation and weaning were also lighter and displayed improved glucose tolerance compared with chow fed animals. We conclude that a high protein diet is a reasonable strategy to reduce body weight gain and improve glucose tolerance in the NZO mouse, a polygenic model of obesity.
Keywords: New Zealand Obese mouse; high protein diet; weight gain; glucose tolerance